2022
DOI: 10.1155/2022/6555005
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Geoecological Restoration in Mountainous Cities Affected by Geological Hazards with Interval Intuitive Fuzzy Information

Abstract: With the progress of the industrial revolution and the development of modern science and technology, China’s urbanization process has been promoted. Urban and rural economic and social construction has greatly improved the local appearance and social structure. Human activities and natural ecology have affected the whole geological-ecological process, further aggravated the geological-ecological damage, and caused more serious geological disasters, especially in some places (especially in mountainous areas). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The current high population density, high population mobility, delayed infrastructure construction, chaotic structural layout, and large building vulnerability in cities have brought a severe test to the safety of cities (6,7). How to solve the weak foundation of urban disaster prevention, how to improve emergency response capability, and how to generally improve the comprehensive disaster prevention capability of cities have become a tough task in the current era (8)(9)(10). It has become a major issue worldwide since the first reported detection of the COVID-19 outbreak in December 2019 (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The current high population density, high population mobility, delayed infrastructure construction, chaotic structural layout, and large building vulnerability in cities have brought a severe test to the safety of cities (6,7). How to solve the weak foundation of urban disaster prevention, how to improve emergency response capability, and how to generally improve the comprehensive disaster prevention capability of cities have become a tough task in the current era (8)(9)(10). It has become a major issue worldwide since the first reported detection of the COVID-19 outbreak in December 2019 (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%